Tindak Tutur Ilokusi Ekspresif pada Tayangan Youtube Catatan Demokrasi TV One Episode “Pagar Laut” - Ramadhani, Dwi Laksanita; Pujihastuti, Etin; Krisnawati, Vera (GERAM (Gerakan Aktif Menulis), 2025)
This study aims to describe the forms of expressive illocutionary speech acts in the YouTube program Catatan Demokrasi TV One, episode "Pagar Laut." The research identifies the use of expressive illocutionary acts in a public discussion forum broadcast through digital media, employing a qualitative descriptive approach. The data source consists of utterances containing expressive illocutionary acts in the episode. Data were collected using the observation method, including techniques such as recording (sadap), non-participatory observation (Simak Bebas Libat Cakap/SBLC), and note-taking to obtain relevant transcripts. Data analysis was conducted using the pragmatic equivalence method, with the Determining Element Sorting technique (PUP) and the Equalizing Comparative Connection technique (HBS) to classify data based on indicators of expressive speech acts and align the findings with Searle's (1979) theory of illocutionary acts. The findings revealed that the three most dominant types of expressive illocutionary acts were expressing gratitude (30%), greeting (25%), and apologizing (15%). Meanwhile, the least common type found was expressing condolences (0%). These findings demonstrate that expressive illocutionary acts not only serve to express the speaker's psychological state but also play a role in maintaining politeness and fostering harmonious interaction in digital political discussions, thereby enhancing communication dynamics among participants in the forum.